CAGE17-2 Cruise Report: Gas hydrate deposits and methane seepages in Storfjordrenna, Northern Flank of Olga Basin, and West Sentralbanken (Barents Sea): Biogeochemical and biological investigations - Panieri, Giuliana; Alexandropoulou, Nikolitsa; Bruvik, Kine L.; Carrier, Vincent; Dessandier, Pierre-Antoine; Dølven, Knut Ola; Valberg, Espen; Fornari, Daniel; Gründger, Friederike; Kurras, Gregory J.; Yao, Haoyi; holm, Truls; et al. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
The main goal of CAGE 17-2 AMGG cruise was to study the gas-hydrate-bearing system and methane emission off south and east of Spitsbergen in Storfjordrenna and the northern flank of Olga Basin (named here Olga craters) respectively, and in the West Sentralbanken. We addressed this through a comprehensive scientific program comprising dives with the MISO-Tow Cam adapted to the multicorer frame from UiT-NPI (TowCam/Multicorer, TCM), methane measurements in sediments, water column, and in air, sediment coring (multicorer + gravity corer), water column and sediment biogeochemistry, microbiology, micropaleontology, and bathymetric mapping. Cruise CAGE 17-2 was also hosting this year’s AMGG research school cruise with masters, PhD and post-doc students participating. The areas investigated were: Storfjordrenna, Pingos site (ca 380 m water depth),Northern Flank of Olga Basin (ca 140 m water depth)West Sentralbanken (ca 200 m water depth) We planned the following activities during the CAGE 17-2 cruise: EM 302 Simrad swath bathymetry mapping to identify seabed morphology Mapping of flare distributionsCTD stations at different water depths and in different areas for measurements ofocean water masses characteristics, andwater sampling for water/gas chemistry and microbiology investigations across methane seeps.TCM surveys (video-camera) to image seabed fluid flow expressions, sites of bacteria mats, crusts and gas bubbles.Repeated deployments with TCM to sample surficial and shallow sediments with respect to microbiology, geochemistry, biogeochemistry, and micropaleontology.Gravity corer for studying sediment biogeochemistry, biomarkers, microbiology, and foraminifera.Scrape sampling to collect rocks and crusts.Gas Chromatographer (GC) to measure methane concentration in the water and sediment samples.Flasks Restek, Electro-Polished Miniature Canister (1000 cc) for air samples. Part of the cruise was supported by NPD, Oljedirektoratet. Special thanks to Rune Mattingsdal, NPD. The cruise may be known as: CAGE17_2